Seasonal fluctuation of total water intake and hydration status among young men and women: a prospective cohort study - Zhang, Jianfen; Zhang, Na; Lu, Junbo; Liu, Shufang; Lin, Yongwei; Ma, Guansheng (Frontiers in Nutrition, 2025)
BackgroundWater intake and hydration status have been reported to fluctuate throughout the year. This study investigated seasonal fluctuations of total water intake and hydration status among young adults in Baoding, China.MethodsThis prospective cohort study enrolled 82 young adults aged 18–23 years in Baoding, China. Total drinking fluids consumed and water from food were assessed, and the osmolality and electrolyte concentrations of 24-h urine and fasting blood samples were determined. Differences among the four seasons were compared by mixed linear models, followed by determinations of least-significant differences (LSD), with spring used as the reference.ResultsSeventy-nine participants (43 men and 36 women) completed the study. Total water intake (TWI) was 359 ~ 429 mL higher in spring and summer than in autumn and winter and was 116 mL higher in summer than in winter (all p < 0.05). Chinese recommendations for TWI were met by 13.9% to 22.8% of participants, and recommendations for total fluid intake were met by 10.1% to 16.5%, but these differences were not statistically significant (p > 0.05). Urinary and plasma biomarkers differed significantly among the four seasons (p < 0.05), with osmolality and urine specific gravity (USG) being significantly higher in summer than in other seasons (p < 0.05). The percentage of participants with optimal hydration status increased from 38.0% in summer to 62.0% in spring (p < 0.05). Men had more concentrated urine as well as higher plasma osmolality and solute concentrations than women during each season of the year (p < 0.05).ConclusionTWI and urinary and plasma biomarkers of hydration were found to vary seasonally among Chinese young adults, with hydration status being poorer in summer. Men need to pay more attention than women to maintain optimal hydration status.Clinical trial registrationhttps://www.chictr.org.cn/showproj.html?proj=124857, ChiCTR2100045268.